2021
DOI: 10.1021/acs.estlett.1c00012
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Algal Blooms in Chinese Coastal Waters Will Persist Due to Perturbed Nutrient Ratios

Abstract: The three large marine ecosystems (LMEs) bordering China (Yellow Sea/Bohai Sea, East China Sea, and South China Sea) have received excess nitrogen (N) and phosphorus (P) in the past decades with detrimental consequences for ecosystem functioning, such as increased productivity, loss of biodiversity, and proliferation of harmful algal blooms (HABs). N loading increased much faster than that of P. Here, we show that HABs in the three LMEs started to proliferate after the N:P molar ratio exceeded the threshold va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…The Changjiang River and Yellow River are two of the largest sources of freshwater to the East China Continental Sea, with annual discharges of 932.3 Â 10 9 and 43.1 Â 10 9 m 3 , respectively (Yincan et al 2017). The East China Continental Sea is also characterized by high productivity (Gong et al 2003), algal blooms (Wang et al 2021), and coastal upwelling (Wang and Wang 2007).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…The Changjiang River and Yellow River are two of the largest sources of freshwater to the East China Continental Sea, with annual discharges of 932.3 Â 10 9 and 43.1 Â 10 9 m 3 , respectively (Yincan et al 2017). The East China Continental Sea is also characterized by high productivity (Gong et al 2003), algal blooms (Wang et al 2021), and coastal upwelling (Wang and Wang 2007).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Große et al [112] estimated that N loading reductions of 50% will be required to reduce the extent of hypoxia. While massive N reductions have a high potential for mitigating blooms and hypoxia (Figures 4(k) and 4(l)) [112], Wang et al [118] showed that because nutrients in China's coastal systems originate from agriculture, aquaculture, industry, and wastewater and, due to the fundamental differences in the biogeochemical cycling of N and P, reductions in N are-and will be-exceedingly difficult to achieve, regardless of the scenario.…”
Section: Case Studies Of Multiple Stressors and Their Complexitiesmentioning
confidence: 99%
“…The average of nutrient ratios in Yangtze River Estuary (Li et al, 2010), Pearl River Estuary (Yin et al, 2001), Jiulong River Estuary and Chinese coastal waters (Wang et al, 2021). Red dashed line represented the threshold of nutrient ratio to inform potential P, N, and Si limitation (Justi ć et al, 1995).…”
Section: Figure 12 |mentioning
confidence: 99%